Study on Ecological Risk Evaluation and Prediction of Cultivated Land in Guangzhou - Huanming LAI; Dafang WU; Yishan LI; Yanyan LIU; Peifang MA; Zhaocheng LI; Yixuan LIANG (Guangdong nongye kexue, 2023)
【Objective】A comprehensive evaluation and prediction of ecological risks of cultivated land in Guangzhou City was carried out to effectively reveal the evolution relationship of between the pattern of cultivated land use and the ecological environment, with a view to serving the construction of ecological civilization in Guangzhou City.【Method】Based on the relative risk model, the study tried to construct a new index system for evaluating the ecological risks of cultivated land, which followed the main risk path of "problem formation-analysis stage -risk characterization-zoning prevention and control". And a comprehensive evaluation of the ecological risks of cultivated land in Guangzhou from 2000 to 2018 was conducted; with the data of various indicators of Guangzhou City at five-year intervals from 2000 to 2015 as initial values, the grey prediction model was used to forecast the ecological risks of cultivated land in the study area in 2020-2025. And corresponding measures to regulate and optimize the ecological risks of regional cultivated land were proposed.【Result】The ecological risk of cultivated land in Guangzhou was at lower risk status from 2000 to 2005, and the average indexes of the comprehensive evaluation of the ecological risk of cultivated land in 2000 and 2005 were 0.3327 and 0.3272, respectively; the ecological risk of cultivated land in Guangzhou was at low risk status from 2010 to 2018, and the average indexes for the comprehensive evaluation of the ecological risk of cultivated land in 2010, 2015 and 2018 were 0.3296, 0.3016 and 0.3078, respectively. Based on the comprehensive evaluation, the cultivated land of low risk- and lower risk- level held a dominant post, and the higher ecological risk areas (Zone Ⅳ) were mainly located in Tianhe District and Huangpu District, and the high ecological risk areas (Zone Ⅴ) located in northeastern of Baiyun District and northwestern of Huangpu District. The ecological risk level of cultivated land in Guangzhou will be at low risk status before 2025, with the predicted risk index of 0.2836.【Conclusion】Based on the above research results, the ecological risk status of cultivated land in Guangzhou shows an improving trend in the past study period, from the lower risk status in 2000-2005 to a low risk status in 2010-2018. In the short to medium term, the ecological risk status of cultivated land in Guangzhou will remain at a low risk level, and the relationship between natural environment, socio-economic development and landscape pattern of cultivated land should be continuously harmonized.